Theoretical and Experimental Research on Air-Conditioning System with Varying Composition Using Non-Azeotropic Refrigerant Mixtures - 蒯大秋; 马一太; 何绍书 (Zhileng xuebao)
On the basis of analyzing the characteristics of changing refrigerating load by means of varying the composition of non-azeotropic mixture and screening the refrigerant mixtures R22/R142b and R32/R124, the testing methods of fixed experience conditions and variable operating conditions have been carried out.The experimental data of the steady state performance have been obtained.It shows that the capacity control can meet the needs of varying refrigerating load with variable working conditions for the non-azeotropic mixtures.